Optimization of the Level of Tapioca Starch in Chicken Meat Caruncles - Singh, Parminder; Sahoo, Jhari; Chatli, Manish K.; Biswas , Ashim K. (Journal of Meat Science, 2014)
The present study was conducted to optimize the level of tapioca starch for the development of chicken meat caruncles (CMC). Three different levels of tapioca starch replacing - 50% (T-1), 60% (T-2) and 70% (T-3) of refined wheat flour, were undertaken along with control (100% refined wheat flour) for this study. All the variants were assayed for physico-chemical, proximate composition, texture profile, colour profile and sensory attributes. The cooking yield (%) was significantly higher (P
Keywords: chicken meat caruncles; Tapioca starch; Spent hen meat; Physico-chemical parameters